A FORESIGHT STUDY ON THE ROLE OF THE EDUCATION QUALITY AND ACCOUNTABILITY UNIT IN ENHANCING STUDENT ACHIEVEMENT MONITORING AND UTILIZING ASSESSMENT RESULTS TO INFORM EDUCATIONAL POLICIES IN JORDAN - Mohammad Ahmad Bani Amer (Adisam Publisher, 2025)
This foresight study aims to explore the role of the Education Quality and Accountability Unit in Jordan in enhancing student achievement monitoring and utilizing assessment results to inform educational policies, with a focus on regional (North, Central, South) and gender disparities. The study adopted a descriptive-analytical approach to provide a comprehensive understanding of school performance levels according to Indicators Five and Six of the Effective School framework. Data were collected from the Education Quality and Accountability Unit reports for the 2023/2024 academic year, providing reliable information on schools’ practices in monitoring student achievement and effectively using individual and cumulative assessment results to support learning and school development plans. Performance was analyzed by region, gender, and standard levels (Low, Medium, and High). The results indicated that the Central region achieved the highest performance levels in both indicators, reflecting systematic and effective assessment practices and higher teacher commitment to documentation and feedback. The North region recorded the lowest performance, highlighting challenges in assessment management and data utilization, while the South showed medium performance, reflecting partial implementation of assessment practices requiring further development. Additionally, female students outperformed males in most regions, indicating greater consistency in learning and assessment practices and higher adherence to self-assessment and assignments, emphasizing the need for interventions that address gender differences. Based on these findings, the study recommends strengthening support for low-performing schools, standardizing and developing assessment practices, effectively using assessment results to improve learning, addressing gender gaps, promoting data-driven decision-making, activating the role of the Education Quality and Accountability Unit, and developing evidence-based national policies to enhance educational quality and equity across Jordan